Analisis Implementasi Penentuan Tingkat Risiko dan Kebutuhan Personel Keselamatan Konstruksi di Proyek Instalasi Pengolahan Air Limbah (IPAL) Kota Palembang - Avicenna; Arie Anggara; Hendra Kelana (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
ABSTRACT In response to the serious issue of workplace accidents, particularly in Indonesia's construction sector, this study examines the effectiveness of Hazard Identification, Risk Assessment, and Risk Control (HIRARC). Focusing on the Palembang City Wastewater Treatment Plant Project, Package A3, the research uses a qualitative case study to analyze the HIRARC process. It investigates the link between identified risk levels and the number of safety personnel assigned to the project. Data were gathered from secondary documents (HIRARC documents and engineering estimates) and primary data from in-depth interviews with key project personnel, including Quantity Surveyors, HSE Engineers, and HSE Inspectors. The findings confirmed the project's classification as